Veterans on Trial : The Coming Court Battles over PTSD - Schaller, Barry R., 1938- (Book collections on Project MUSE., 2012)
Experts anticipate that more than 350,000 veterans of the wars in Iraq and Afghanistan will return to civilian life with posttraumatic stress disorder (PTSD). Barry R. Schaller, a judge and a bioethicist, chronicles the events leading to what he predicts will be the most challenging PTSD epidemic in U.S. military history. Although combat veterans have experienced similar disorders in previous wars, Schaller explains why these two contemporaneous wars in particular are a breeding ground for the condition.